Preparation and Physicochemical Properties of High-Temperature-Resistant Polymer Gel Resin Composite Plugging Material - Tao Wang; Weian Huang; Jinzhi Zhu; Chengli Li; Guochuan Qin; Haiying Lu (Gels)
Lost circulation has become one of the important problems restricting the speed and efficiency of oil and gas drilling and production. To address severe drilling fluid losses in high-temperature fractured formations during deep/ultra-deep well drilling, this study developed a high-temperature and high-strength gelled resin gel plugging system through optimized resin matrix selection, latent curing agent, flow regulator, filling material, etc. Comparative analysis of five thermosetting resins revealed urea-formaldehyde resin as the optimal matrix, demonstrating complete curing at 100–140 °C with a compressive strength of 9.3 MPa. An organosilicon crosslsinker-enabled water-soluble urea-formaldehyde resin achieved controlled solubility and flow–cure balance under elevated temperatures. Orthogonal experiments identified that a 10% latent curing agent increased compressive strength to 6.26 MPa while precisely regulating curing time to 2–2.5 h. Incorporating 0.5% rheological modifier imparted shear-thinning and static-thickening behaviors, synergizing pumpability with formation retention. The optimal formula (25% urea-formaldehyde resin, 10% latent curing agent, 10% high-fluid-loss filler, 0.5% rheological modifier) exhibited superior thermal stability (initial decomposition temperature 241 °C) and mechanical integrity (bearing pressure 13.95 MPa in 7 mm wedge-shaped fractures at 140 °C). Microstructural characterization confirmed interlocking crystalline layers through ether-bond crosslinking, providing critical insights for high-temperature wellbore stabilization.